Climate Refugees: The Unseen Victims of Ecological Crisis - Kunnath, Joby (Asian Horizons, 2024)
The climate crisis and the ecological problems that we are facing today is reshaping our world, as the climate of our common home is changing in an alarming phase at any point in the history of our earth. Along with social, economic, and environmental problems, climate change can also adversely affect the food, water, and economic security of the common people and nation. Another effect of climate change which this article would like to highlight is its impact on the displacement (forced or voluntary displacement) of person. This article presents the problems of climate migrants/refugees, which are often not noticed by the international community. Recently, the UN and many developed nations have taken certain actions to cushion the problems of these people. Pope Francis was a forerunner in this matter, and he explained clearly their issues in his encyclical Laudato Si’. After taking this issue to the public with the writings, speeches and deeds of Pope Francis, world leaders also began to respond to the needs of climate refugees.